An Analysis of Figurative Language in Taylor Swift’s Songs - Sandjaja, Angelina; Afriana, Afriana (LPPM Universitas Bumigora Mataram, 2025)
The study aimed to explore the figurative language used in Taylor Swift’s songs, with an emphasis on identifying the various types of figurative language employed. The descriptive qualitative research method was used to identify and analyze the figurative language present in the songs of Taylor Swift. This approach involved a detailed examination of the lyrics, focusing on categorizing and interpreting various forms of figurative language. Utilizing a theory developed by Greg Johnson and Thomas Roscoe Arp, in collecting the data, the researcher used a non-participation technique. The songs of Taylor Swift served as the object of this investigation. The findings of this study indicated that 18 data of figurative language were identified and categorized. The researchers discovered that simile was the most prevalent form of figurative language. Figurative language was found in several of Taylor Swift’s songs, including